2012
DOI: 10.1177/0269215512439727
|View full text |Cite
|
Sign up to set email alerts
|

A periodized model for exercise improves the intra-hospital evolution of patients after myocardial revascularization: a pilot randomized controlled trial

Abstract: Objective: To compare models of the postoperative hospital treatment phase after myocardial revascularization. Design: A pilot randomized controlled trial. Setting: Hospital patients in a hospital setting. Subjects: Thirty-two patients with indications for myocardial revascularization were included between January 2008 and December 2009, with a left ventricular ejection fraction (LVEF) ≥50%, 1-second forced expiratory volume (FEV1) ≥60 and forced vital capacity (FVC) ≥60% of predicted value. Interventions: Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…One study ( de Macedo et al, 2012 ) assessed the impact of block periodized training on the intra-hospital evolution of patients following myocardial revascularization. Participants were randomized to receive respiratory and motor exercise prescriptions during time within the intensive care unit (ICU) and during hospitalization in room based on recommendations from the American College of Sports Medicine (ACSM) or based on block periodization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study ( de Macedo et al, 2012 ) assessed the impact of block periodized training on the intra-hospital evolution of patients following myocardial revascularization. Participants were randomized to receive respiratory and motor exercise prescriptions during time within the intensive care unit (ICU) and during hospitalization in room based on recommendations from the American College of Sports Medicine (ACSM) or based on block periodization.…”
Section: Resultsmentioning
confidence: 99%
“…Periodization advocates the strategic use of variable workloads over time. Although periodized methods are purported to be superior to non-periodized methods in trained populations ( Fry et al, 1992a , Fry et al, 1992b , Rhea and Alderman, 2004 ), only two ( de Macedo et al, 2012 , Klijn et al, 2013 ) of the 21 included studies compared periodized and equivalent non-periodized training in sedentary populations, highlighting a substantial limitation in this body of research. While both studies found that periodized training yielded greater health and fitness effects, it is premature to determine superiority over non-periodized exercise prescriptions in untrained adults.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its wide use for improving sports performance, the periodized model seems to yield greater benefits for risk factors of cardiovascular diseases and for improved quality of life [13]. While the benefits of periodization have been previously evidenced, few studies have used a model not periodized in its comparison to understand the difference between the methods employed [14,15]. Therefore, improving the knowledge of responses to linear periodization and non-periodization, with equal total volumes, will contribute to more efficient training models and improved health in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model can be subjective, since exercise prescriptions are made on the basis of the therapist's knowledge of previous management of similar patients, patient fatigue, patient readiness and pain. [2][3][4] One could also hypothesize whether the evident lack of adequate training principles is the main cause for patients not being able to progress appropriately with their rehabilitation programmes. 3 Alternatively, another model of exercise prescription that is finding its way into the field of rehabilitation is known as periodization.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] One could also hypothesize whether the evident lack of adequate training principles is the main cause for patients not being able to progress appropriately with their rehabilitation programmes. 3 Alternatively, another model of exercise prescription that is finding its way into the field of rehabilitation is known as periodization. 5,6 The difference between the ACSM-guided exercise programmes and periodization is that it involves planned training variations relating to the volume, intensity and frequency of exercises.…”
Section: Introductionmentioning
confidence: 99%